Evaluation of the analgesic effect of maropitant in cats submitted to elective ovariohysterectomy - Garcia, Cinthia (Pubvet, 2021)
The aim of this study was to analyze the analgesic effect of maropitant, compared to isolated morphine or combination of both drugs, when used as pre-anesthetic medication in elective ovariohysterectomy procedure in feline species. The physiological parameters and anesthetic plan of 18 cats in the trans-surgical period were evaluated, in addition to the behavior in 2, 4, 6, 8, 12 and 24 hours post-surgery using the Visual Analogue Scale and the Multidimensional Scale of Acute Pain in Felines for two treatment-blind evaluators. It can be concluded that the use of maropitant alone or associated with morphine had the same analgesic efficacy as morphine.
Keywords: Behavior; ache; cats